VISUM (Virtual Tour of 18th Century Lasem History) for Historical Learning - Wijaya, Daya Negri; Wahyudi, Deny Yudo; Nafi'ah, Ulfatun; Mufti, Muhammad 'Afwan (UNIVERSITAS MUHAMMADIYAH METRO, 2026)
This article examines the potential of virtual tour technology as an innovative educational tool to study the Yellow War in Lasem, a pivotal event in Indonesian history in the 18th century. By developing an immersive virtual environment and accompanying educational guidebook, the virtual tour allows users to explore the landscape and key locations associated with the conflict while engaging with its narrative. The integration of written and oral history sources enhances the learning experience, encouraging a deeper understanding of the Yellow War and its significance in Indonesia's past. This article discusses the design considerations involved in creating an effective virtual tour, the educational benefits it offers, and its wider implications for history learning. The article emphasizes how virtual tour technology can actively engage and educate diverse audiences, making historical events more accessible and relatable. Through this dynamic and immersive approach, users can gain insight into the complexities of the Yellow War, ultimately contributing to a more nuanced understanding of Indonesian history. The findings suggest that virtual tour technology has the potential to revolutionize history learning, providing an engaging platform for learning and exploration.